2019
DOI: 10.1039/c9ra01133a
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous bioactive glass nanoparticles doped with magnesium: drug delivery and acellular in vitro bioactivity

Abstract: The effects of the magnesium doping of binary glass (Si–Ca) on particle texture, on the biomineralization process in simulated body fluid (SBF) as well as on drug loading and release were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 60 publications
(83 reference statements)
5
53
0
Order By: Relevance
“…Adding to this, the mesoporous nanoparticle form of bioactive glass has the capacity to intracellular deliver therapeutic molecules (drugs, growth factors, or genes) [ 16 ]. Some of the recent studies have reported that mesoporous bioactive glass nanomaterials and their composites/hybrids could demonstrate the capacity for delivering drugs and genes, as well as releasing bioactive ions [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
“…Adding to this, the mesoporous nanoparticle form of bioactive glass has the capacity to intracellular deliver therapeutic molecules (drugs, growth factors, or genes) [ 16 ]. Some of the recent studies have reported that mesoporous bioactive glass nanomaterials and their composites/hybrids could demonstrate the capacity for delivering drugs and genes, as well as releasing bioactive ions [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ].…”
Section: Introductionmentioning
confidence: 99%
“…Arepalli et al reported that bioactive glasses in the system (46.10-x)%SiO2-26.9%CaO-24.40%Na2O-xMgO-2.6%P2O5 (where 0≤x≤3 mol %) are bioactive and biocompatible both in vitro and in vivo 14,24 . It is well reported that magnesium slows down the crystallization of the apatite layer 16,17 , however, in this work we report the formation of an apatitelike phase after 1 h of soaking in SBF as it can be seen in Figure 3. Additionally, the growth of apatite layer continues to occur as it can be observed from the pattern of SNCMP glass after 30 d of immersion in SBF solution.…”
Section: Resultsmentioning
confidence: 45%
“…It was found that the incorporation of MgO in the bioactive glass accelerates the early stages of the precipitation of HAC layer 15 . However, some studies have reported that MgO slows down the precipitation rate of HAC 16,17 . Tabia et al have shown that there is no crystallization of HAC layer when magnesium attaint 10 mol % in the ternary bioactive glass 85SiO2-(15-x)CaO-xMgO (where x = 0, 1, 3, 5 and 10) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Tabia et al [192] fabricated the Mg-doped bioactive glass nanoparticles (BG-NPs) through the sol-gel route. They loaded amoxicillin to the synthesized BG-NPs and investigated their drug release behavior.…”
Section: The State-of-the-art Of Composites Containing Zn and Mg In Dmentioning
confidence: 99%